Turner syndrome and its profile: A single centre Malaysia study - Abu Ishak, Nurkhairulnisa; Abdul Ghani, Nur Azurah; Zainuddin, Ani Amelia; Ali, Anizah (Malaysian Medical Association, 2021)
Nurkhairulnisa Abu Ishak1, Nur Azurah Abdul Ghani2, Anizah Ali2, Ani Amelia Zainuddin2 1Department of Obstetrics and Gynaecology, Kulliyyah of Medicine, International Islamic University of Malaysia, 2Department of Obstetrics and Gynaecology, Universiti Kebangsaan Malaysia Medical Centre